Analisis Yuridis Tanggung Jawab Perusahaan Asuransi Terhadap Asuransi Jiwa Kredit: Studi Putusan Nomor 3079K/PDT/2019 - Rahma Selina Yustika Yanti; Arief Suryono (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
The aim of this research is to investigate the regulations governing the position of the insured in credit life insurance and the responsibilities of insurance companies, as delineated in Decision Number 3079K/Pdt/2019. Credit life insurance serves as a mechanism for banks to mitigate the risk of debtor default in debt repayment resulting from the death of the debtor. It entails a collaborative effort between banks and insurance companies aimed at facilitating credit repayment to the bank in the event of the demise of the credit facility user (debtor). This research adopts a normative legal approach with a case study methodology, examining legal issues elucidated in court decisions of enduring legal significance. The findings from Decision Number 3079K/Pdt/2019 reveal that the insurance company bears the responsibility of settling the outstanding debt of the insured, contingent upon premium payments, in the event of the insured's demise. In the realm of insurance, the direct relationship typically exists between the insured and the insurer; however, in credit life insurance, the direct relationship materializes between the insurer and the policyholder, thereby rendering the position of the insured comparatively weak and indirect.